PENGARUH TUNJANGAN PROFESI (REMUNERASI), PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA POLISI PADA POLRES MUNA - Zainal Arifin; La Hatani; La Ode Asfahyadin Aliddin (Pascasarjana Universitas Halu Oleo, 2021)
The purpose of this research is to test and explain the influence of professional allowances (remuneration), education and training on police performance both simultaneously and partially at the Muna Police Station. This research approach is quantitative with a positivist paradigm. Data was collected by cross-section by using a questionnaire. The population of this research is all police personnel with the rank of AIPDA and BRIPKA as many as 252 people. The sample size was determined by the Slovin formula, so that a sample of 71 people was obtained. The sampling technique is based on random sampling. The analytical tool used is Multivariate Regression Analysis. The results showed that the professional allowance (remuneration), education and training simultaneously had a positive and significant effect on police performance. Then the professional allowance (remuneration) partially positive and significant effect on police performance. Education partially has a positive and significant effect on police performance. Training has a positive and partially significant effect on police performance. This means that the higher the professional/performance allowance, education and training, the police performance will increase significantly. Changes in the increase in professional/performance allowances which are described by the fulfillment of requirements in receiving professional/performance allowances (remuneration), education, namely the opportunity for the development of knowledge through formal education, then training, namely the clarity of goals and targets for participating in training, has a significant or significant contribution to the improvement police generic police performance.